P89 THE HEART TEAM SUCCESS: TAVI IN–VALVE IN A COMPLEX PATIENT. (18th May 2022) - Vecchio, C; Calderone, D; Oreglia, J; Nassiacos, D
Abstract: CG was a 80–years–old man with normal BMI, arterial hypertension and CAD family history.He suffered OSAS needs nocturnal cPAP, MGUS, colon diverticulosis and CKD in dialysis treatment since 2006 after right nephrectomy for adenocarcinoma and wrinkle left kidney for focal glomerulosclerosis since 1982.Note valvular heart disease with mitro–aortic insufficiency: in 6/2010 he performed aortic valve replacement with Carpentier Perimount 23 bioprosthesis, mitral annuloplasty with St Jude 28 ring and surgical revascularization with single graft on PDA coronary.During post–surgical period transients III degree AVB and AF were observed with subsequent restoration and stabilization in sinus rhythm.In 5/2011, thanks to Holter registration of stable sinus rhythm, VKA anticoagulation was stopped and only ASA continued.In 1/2013 well tolerated AF was found then VKA resumed.In 6/2016 during the follow up the echocardiogram showed hypertrophic and hypokinetic left ventricle, EF 45%, moderate biatrial dilatation, normofunctioning aortic bioprosthesis with mild aortic root and first ascending tract dilatation and successful mitral annuloplasty.In 3/2018 worsening exertional dyspnea with initial heart failure were documented and echocardiography showed aortic bioprosthesis degeneration with severe stenosis and mild intraprosthetic insufficiency, preserved EF, mild mitral steno–insufficiency, normal right sections with mild–moderate tricuspid insufficiency and mild pulmonary hypertension.In 6/2018 the subsequent coronary angiography evidenced venous graft occlusion and critical RCA stenosis treated by PTCA+DES Biofreedom in the middle segment: triple therapy with ASA, clopidogrel and VKA indicated for one month.One month later, in 7/2018 TAVI was performed on aortic bioprosthesis with Portico n.23 prosthesis: in the post–procedural phase mild anemia and positive FOB were found. The patient presented high both thrombotic and bleeding risk because of persistent AF, recently coronary reperfusion with DES and dialysis treatment so we decided to close left atrial appendage by Watchman system and keep on single antiplatelet therapy with ASA. Pre and post procedures dialysis treatments were performed without complications.Subsequent clinical and echocardiographic follow up without complications.The diagnostic–therapeutic iter sharing in Heart and multi–specialists team has favored the best timing of treatment and the success of procedures in a very high cardiovascular risk patient.